2021
DOI: 10.3390/foods10071504
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Erythromycin and Clarithromycin Metabolites Formed in Chicken Liver Microsomes Using Liquid Chromatography–High-Resolution Mass Spectrometry

Abstract: Nontargeted analysis can be used for the rapid screening and confirmatory analysis of veterinary drugs and their metabolites, which are important for the comprehensive safety evaluation of animal-derived foods. Here, a novel nontargeted screening approach based on liquid chromatography coupled with electrospray ionization–high-resolution mass spectrometry (LC/ESI–HR-MS) was developed to determine erythromycin, clarithromycin, and their metabolites in chicken liver microsomes. Erythromycin and clarithromycin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Various analytical methods, including HPLC–MS/MS ( Campanharo et al, 2023 ), HPLC with UV diode array detection (DAD) ( Cañadas et al, 2022 ), electrochemical sensors ( Lai et al, 2023 , Li et al, 2022 ), TLC densitometric methods ( Sharkawi et al, 2023 ), and UHPLC–MS/MS ( Du et al, 2021 ), have been used for identifying ERY, CLA and other MACs in fish, milk, honey, egg and animal tissues. In previous studies, Wang et al (2021 ) developed an LC with a time-of-flight (ToF)-MS/MS method to verify whether ERY and CLA can produce N -desmethyl metabolites in chicken liver microsomes. The results showed that ERY produced N - d -ERY in chicken liver microsomes after incubation for 60 min and after an NADPH cofactor was added.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various analytical methods, including HPLC–MS/MS ( Campanharo et al, 2023 ), HPLC with UV diode array detection (DAD) ( Cañadas et al, 2022 ), electrochemical sensors ( Lai et al, 2023 , Li et al, 2022 ), TLC densitometric methods ( Sharkawi et al, 2023 ), and UHPLC–MS/MS ( Du et al, 2021 ), have been used for identifying ERY, CLA and other MACs in fish, milk, honey, egg and animal tissues. In previous studies, Wang et al (2021 ) developed an LC with a time-of-flight (ToF)-MS/MS method to verify whether ERY and CLA can produce N -desmethyl metabolites in chicken liver microsomes. The results showed that ERY produced N - d -ERY in chicken liver microsomes after incubation for 60 min and after an NADPH cofactor was added.…”
Section: Resultsmentioning
confidence: 99%
“…Both erythromycin A (ERY) and clarithromycin (CLA), two MACs that share comparable antibacterial processes and have an impact on both gram-positive and gram-negative bacteria, are members of the same class ( Juan et al, 2010 ). In our previous study, the major metabolite of ERY in chicken liver microsomes was determined to be N -desmethyl-erythromycin A ( N - d -ERY) ( Wang et al, 2021 ). Reports have indicated that N - d -ERY does not possess antibacterial activity; however, N - d -ERY represents a potential risk to individuals ( Lundquist et al, 2014 , Sun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…At least 500 kinds of macrolide antibiotics are known, most of which are derived from Streptomyces species. The frequently used macrolide antibiotics are erythromycin [ 1 ], oleandomycin [ 2 , 3 ], josamycin [ 4 , 5 ], midecamycin [ 4 , 6 ], spiramycin [ 7 , 8 ], roxithromycin [ 9 , 10 ], azithromycin [ 11 , 12 ], and clarithromycin [ 13 , 14 ]. Macrolides exhibit high activity against Gram-positive bacteria, and are thus used widely as excellent bacteriostatic agents due to their low toxicity and broad-spectrum activities.…”
Section: Introductionmentioning
confidence: 99%